Tribological properties of Cr- and Ti-doped MoS2 composite coatings under different humidity atmosphere - Ding, Xing-zhao. (2012)
Solid-lubricant MoS2 coatings have been successfully applied in high vacuum and aerospace environments. However, these coatings are very sensitive to water vapor and not suitable for applications in moist environments. In this work, Cr- and T-doped MoS2 composite coatings were developed. The results demonstrated that these composite coatings are promising for applications in high humidity environments.